2021
DOI: 10.3390/su13168971
|View full text |Cite
|
Sign up to set email alerts
|

The Individual Dimension of Digital Innovation: The Altered Roles of Innovation Agents and Market Actors

Abstract: Digital innovation entails the employment of new technologies to address business issues and to create practices that lead to the achievement of sustainability. It is observed that digital technology alters the individual dimension of the innovation process, allowing for a set of heterogenous actors to become active engagers in the process. A review of the previous research revealed a lack of focus on the roles these different actors play in the digital innovation process, as well as the mechanisms by which di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It is observed that digital technology alters the individual dimension of the innovation process, allowing for a set of heterogeneous actors to become active engagers in the adoption process. A review of previous research revealed a lack of focus on the roles these different actors play in the digital innovation process, as well as the mechanisms by which digital technology facilitates actor engagement, calling for research to shed some light on this topic (Allataifeh & Moghavvemi, 2021;Yang et al, 2021). In this study, traits connected with the perception of BDM and ERMS expected outcomes, and which help one in one's adoption of BDM are classified as individual traits.…”
Section: Individual Dimensionmentioning
confidence: 99%
“…It is observed that digital technology alters the individual dimension of the innovation process, allowing for a set of heterogeneous actors to become active engagers in the adoption process. A review of previous research revealed a lack of focus on the roles these different actors play in the digital innovation process, as well as the mechanisms by which digital technology facilitates actor engagement, calling for research to shed some light on this topic (Allataifeh & Moghavvemi, 2021;Yang et al, 2021). In this study, traits connected with the perception of BDM and ERMS expected outcomes, and which help one in one's adoption of BDM are classified as individual traits.…”
Section: Individual Dimensionmentioning
confidence: 99%
“…Therefore, scholars recommend focusing on dynamic models, which would readily adapt to changing contexts. Developing such dynamic models involves examining and explaining the digital innovation process in terms of the interplay between the market and technological dimensions of the innovation process and the need-solution pairing perspective (Allataifeh and Moghavvemi, 2021;Makkonen and Komulainen, 2018;Nambisan et al, 2017;von Hippel and von Krogh, 2016).…”
Section: The Digital Innovation Process and Its Market And Technology...mentioning
confidence: 99%